PHYSICAL ACTIVITY AND ITS IMPORTANCE FOR THE PREVENTION OF CARDIOVASCULAR DISEASES - S. S. Yakushin; E. V. Filippov (Klinicist)
Lack of physical activity (PA) is today one of the most important risk factors for atherosclerosisrelated deaths. Its level is falling worldwide. A study in the UK, USA, India, Brazil and China (45 % of the world population) total PA declined in these countries and will continue to fall over the next 15 years. In Russia, the level of the PA population decreased. PA is responsible for 12.2 % of the global burden of myo cardial infarction. These more than 40 observational studies demonstrate the complete proofs of the linear relationship between the level of PA and total mortality in younger and older men and women. The minimum threshold PA, which can reduce the risk of allcause mortal ity is at a level of 2.5–5 hours a week. Further increase of the PA (its duration and/or intensity) leads to a further reduction of risks. PA should take most days of the week and have a duration of more than 10 minutes a day. Only then did she summed up. In patients with cardiovascular disease to determine the necessary level of PA is difficult. Therefore, before the training they have to undergo stress testing. The program of training should be determined on the basis of findings and the clinical status. Even brief moderate and/or intense exercise can reduce the risk of death of the patient. If an individual does not reach the target of 150 minutes of moderate PA per week, but has been a regular, his risk of CHD was significantly reduced (14 %, 95 % CI 0.76–0.97). The development of programs to improve the PA of the population can have a significant impact on the overall and cardiovascular mortality.